METACOGNITIVE STRATEGY INSTRUCTION IN EFL CLASSROOMS: A SYSTEMATIC REVIEW - Suharto, Pipit Prihartanti; Damayanti, Ika lestari; Lengkanawati , Nenden Sri (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
Metacognitive strategies stimulate an individual's thoughts, resulting in enhanced learning performance. Utilizing such learning strategies encourages students to reflect on their cognitive processes before, during, and after learning. The present study seeks to review the literature on teaching metacognitive strategies explicitly in English as a foreign language (EFL) classrooms. Data collection and analysis followed Newman & Gough's (2020) systematic review procedure. This review begins with a summary of the results of 36 studies on the subject. Based on the summaries, the review draws general conclusions and suggests future research directions. The review identifies a need for more intervention-based research conducted in the primary English classroom that implements metacognitive strategies, focusing not only on a single language skill or language element but also on integrated skills during regular teaching hours. Keywords: learner training; metacognitive intervention, metacognitive strategies; strategy instruction; strategy training